The Construction of an Undergraduate Creativity Seminar 33 Years in the Making - Beth A. Hennessey (Education Sciences, 2022)
For 33 years, I offered an undergraduate, upper-level seminar on the Psychology of Creativity. A review of nearly three dozen versions of seminar syllabi, readings, assignments and student work reveals a chronicling of the evolution of the study of creativity as well as the evolution of classroom teaching, student sensibilities, and my own changing views.